Influence of Motivational Interviewing on Explicit and Implicit Alcohol-Related Cognition and Alcohol Use in At-Risk Adolescents - Thush, Carolien (2009)
Both implicit and explicit cognitions play an important role in the development of addictive behavior. This study investigated the influence of a single-session motivational interview (MI) on implicit and explicit alcohol-related cognition and whether this intervention was successful in consequently decreasing alcohol use in at-risk adolescents. Implicit and explicit alcohol-related cognitions were assessed at pretest and one month posttest in 125 Dutch at-risk adolescents ranging in age from 15 to 23 (51 males) with adapted versions of the Implicit Association Test (IAT) and an expectancy questionnaire. Motivation to change, alcohol use and alcohol-related problems were measured with self-report questionnaires, at pretest, at posttest after one month, and at the six-month follow-up. Although the quality of the intervention was rated positively, the results did not yield support for any differential effects of the intervention on drinking behavior or readiness to change at posttest and six-month follow-up. There were indications of changes in implicit and explicit alcohol-related cognitions between pretest and posttest. Our findings raise questions regarding the use of MI in this particular at-risk adolescent population and the mechanisms through which MI is effective.